The Complex Conjunction “kako god što” in the Fifth Decade of the 19th Century, with Reference to Administrative-Legal Style - Pavlović Jovanović, Jelena M.; Spasić, Nataša A. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
This paper examines the status of comparative and manner-comparative clauses introduced by the complex conjunction kako god što in the administrative-legal style of the Serbian language in the 19th century. The study was motivated by a linguistic gap: the conjunction is absent from contemporary grammatical descriptions and spoken usage, raising questions about its historical role and gradual disappearance. Since legal language often preserves archaic constructions missing from other functional styles, analyzing this structure is crucial for understanding the evolution of administrative discourse. The corpus consists of legislative texts from the Collection of Laws, Regulations, and Decrees (1840, 1845), providing empirical data on the frequency, function, and syntactic role of kako god što. A descriptive qualitative approach was applied to identify and classify comparative and manner-comparative clauses according to syntactic and semantic features. Findings indicate that kako god što was primarily used in pre-standardization legal texts, with dependent clauses consistently appearing within the prepositional phrase, while the main clause was introduced by the correlational element tako. The conjunction reinforces qualitative equivalence between legal norms. In dependent clauses, the dominant verb forms are the present tense and the future tense I, whereas main clauses frequently include imperative constructions. The study suggests that the gradual disappearance of kako god što from standard language is linked to broader syntactic and legislative modernization processes, offering a foundation for comparative analysis with other Slavic languages in historical syntax research.